The Role of Nutritionist Personality in Efforts to Reduce Stunting at Mantrijeron Health Center, Yogyakarta City - Prita Astungkara; Winarno Winarno; Purbudi Wahyuni (Westscience Press, 2023)
Short toddlers are toddlers with nutritional status based on length or height for their age when compared to the WHO-MGRS (Multicentre Growth Reference Study) standard in 2005. Stunting is a condition of growth failure in infants (0-11 months) and children under five (12-59 months) due to malnutrition since the baby is in the womb and in the early period after the baby is born. Indonesia, especially Yogyakarta City, is an area affected by cases of short toddlers with poor nutritional status as many as 1225 cases where the Mantrijeron Health Center is the health center with the highest stunting cases in Yogyakarta City. Nutritionists are considered the frontline in terms of identifying public health and nutrition problems, especially in pregnant women and toddlers, which may trigger high stunting rates in Indonesia. The personality of the Nutritionist, seen from The Big Five Personality is considered capable of generating client interest in conducting regular consultations and being able to live a healthy life in the hope of suppressing the growth of stunting rates. The results of the study stated that the openness to experience dimension was absent in one of the Nutritionists as seen from the difficulty in adjusting the language and the obstruction of work due to lack of mastery of digital technology.